Konsep Kampus Merdeka Belajar di Era Revolusi Industri 4.0 - Siregar, Nurhayani; Sahirah, Rafidatun; Harahap, Arsikal Amsal (Fitrah: Journal of Islamic Education, 2020)
Lately, there has been a lot of discussion in the world of education, with the concept of freedom of learning being coined by the minister of education and culture, Nadiem Makarim. in terms of including the concept of a free campus of learning. the concept becomes an effort in dealing with the changing times. then how is the concept of an independent campus learning in the face of the industrial revolution era 4.0. and how the concept of an independent campus that had been sparked by the Minister of Education and Culture namely Mr. Nadiem Makarim as well as what is the problem of students at this time so that it requires a change in the concept of higher education for the better. considering that in this case, the era of the industrial revolution 4.0 is an era in which technology is increasingly high, so that in this case students from each tertiary institution are expected to be ready to face challenges in the industrial revolution era 4.0, with the concept of an independent campus they are directed to be more ready to work , working together, creative and can be useful for themselves and other communities.